The Influence of Learning Motivation on the Learning Activities of Grade XI Students at Muhammadiyah 3 Vocational School Makassar - Putri Amalia Ilyas; Sirajuddin Saleh; Muh Nasrullah (Journal of Educational Development and Learning (JEDAL), 2025)
Learning motivation is critical for students because it can improve student learning activities such as having a passion for learning, participating in active learning activities, and achieving optimal learning outcomes. This study aims to determine the effect of learning motivation on the learning activities of grade XI students at SMK Muhammadiyah 3 Makassar. Learning motivation is an important factor that influences the quality and quantity of student involvement in the learning process. This study uses a quantitative approach; this study involved 63 grade XI students as research samples selected through proportional random sampling techniques. Data was collected through a questionnaire consisting of two main parts: learning motivation and learning activities. The results indicated that the indicators for each variable revealed learning motivation to be in the low category, whereas student learning activities were categorized as high. The indicators of learning motivation were intrinsic motivation and extrinsic motivation. Indicators of learning activities were viewing activities, oral activities, and listening activities. Based on a simple linear regression analysis, it was concluded that there was a significant influence between learning motivation and student learning activities at SMK Muhammadiyah 3 Makassar.